Role of digital platform, network capability and organizational readiness to reinforce innovation in the pandemic era - Gege Raharjo; Avanti Fontana (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Digital consumption is now a new lifestyle. Sixty million consumers who have just joined since the pandemic will remain, with nine out of ten consumers who tried new digital services in 2020 and will continue to use the service. Forty million new Internet users in 2021 will increase digital penetration in Southeast Asia by 75%, and eight out of ten of these users have bought something online at least once. This shows the enormous potential of the digital economy in Southeast Asia, and Indonesia is no exception. In the era of new technological advancements, it is not surprising that sophisticated information systems facilitate organizational innovations to achieve a competitive and collaborative advantage. It will remain a major topic of interest for researchers and practitioners. The business world is increasingly adopting information technology (IT) and digital business. Therefore, the role of IT in business is particularly important in the digital economy to achieve innovation. One of the most key factors of digital technology and the innovation process is the emergence of digital platforms at the heart of innovation. The development of digital platforms has shifted the focus of value creation from linear inter-organizational relationships toward interconnected networks. A study by Larsen and Roberts in 1971 noted that about 90% of ideas generated failed for implementation. This study seeks to address the roles of digital platform capabilities in improving or increasing the innovation performance of established companies.